The Role of Habits in Shaping Future Criminal Behavior: A Forensic Perspective - Salsabila Kalizta; Muhamad Yuda Maryanto; Jefri Firnando (Jurnal Sosial Indonesia, 2026)
This research explores the critical role of habitual behavior in shaping future criminal conduct, particularly within forensic psychology. Habitual behavior, which involves repeated actions that become ingrained over time, significantly increases the likelihood of recidivism, particularly among offenders engaged in violent or drug-related crimes. The study aims to examine how habitual patterns of criminal behavior contribute to the persistence of criminal activity and how forensic psychology can offer insights for effective intervention. A systematic literature review was conducted using databases such as PubMed, PsycINFO, and Scopus, focusing on peer-reviewed articles related to habitual behavior, recidivism, and psychological intervention. The findings reveal that habitual offenders are at a heightened risk of re-offending due to entrenched behavioral patterns and the reinforcing effects of addiction and social environments. The research emphasizes the importance of rehabilitation programs, including cognitive-behavioral therapy, that target these ingrained behaviors to reduce recidivism. The study underscores the need for a more comprehensive approach to criminal rehabilitation, focusing on the psychological, social, and environmental factors that perpetuate habitual offending.